Pengaruh Disiplin dan Motivasi Kerja terhadap Prestasi Kerja Karyawan pada CV Arga Jaya Konstruksi Kota Depok - Olivia Zahra Khairyama; Taat Kuspriyono; Yunidyawati Azlina (Fakultas Ekonomi & Bisnis, Univ, 2025)
Employee performance is not merely a benchmark stipulated by an organization; rather, it constitutes a pivotal determinant that substantially contributes to the attainment of corporate objectives and long-term sustainability. Superior performance illustrates the extent to which employees are capable of executing their designated responsibilities, which subsequently exerts a direct influence on organizational productivity, efficiency, and growth trajectory. Among the multidimensional variables affecting performance, two particularly salient aspects are work discipline and work motivation. Discipline functions as a regulatory mechanism that ensures adherence to established norms, policies, and operational procedures, while motivation operates as an internal drive that fosters persistence, engagement, and consistency in accomplishing tasks. Collectively, these two dimensions are assumed to exert a decisive influence on performance outcomes. The present study endeavors to examine the impact of work discipline and work motivation on employee performance within CV Arga Jaya, located in Depok City. Employing a quantitative research design, this investigation utilizes multiple linear regression analysis facilitated through SPSS version 27. The study encompasses a population comprising employees from both administrative and operational divisions, yielding a total of 43 valid respondents. Data were elicited through the administration of structured questionnaires as the principal instrument. The empirical results reveal that work discipline (X1) and work motivation (X2) simultaneously exert a significant influence on performance (Y), corroborated by an F-count of 6.38 exceeding the F-table value of 3.23 with a significance level of 0.004. Partial Alexistoto analysis indicates that work discipline (X1) has a significant positive impact, with a T-count of 2.377 surpassing the T-table threshold of 2.021. Conversely, work motivation (X2) demonstrates no significant partial effect, as evidenced by a T-count of 1.339 and a significance level of 0.188. The coefficient of determination (R²) of 0.242 suggests that 24.2% of the variation in performance is explained by these factors, whereas 75.8% is attributable to variables beyond the scope of this study.